Faktor yang berhubungan dengan kecemasan terinfeksi covid-19 pada tenaga kesehatan di Puskesmas Kota Pontianak - Amaliya Irmayanti; Elly Trisnawati; Ismael Saleh (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2021)
Abstract Background : Covid-19 is still a health problem in West Kalimantan. One of the cities with the highest contributor to Covid-19 cases is Pontianak City. Covid-19 sufferers in Pontianak City have spread to various groups including health workers who are at the forefront of handling Covid-19. Health workers, especially doctors and nurses, are the group most at risk of contracting Covid-19 during their activities in health care facilities (fasyankes). The increasing number of Covid-19 cases in the general public can trigger anxiety in health workers. This anxiety can have an impact on work productivity and decrease the immunity of health workers. This study aims to determine the factors associated with anxiety about Covid-19 infection among health workers at the Pontianak City Health Center.Method : This type of research is a quantitative (analytic observational) study with a cross sectional design. The number of samples was 87 health workers (doctors and nurses) in Pontianak City puskesmas who were taken through accidental sampling technique. Data collection is done by retrieving data online using google formular. Data were analyzed bivariately with the Ch-Square test.Results : The results showed that there was no relationship between the age of the respondent (p value = 0.183 and the gender of the respondent (p value = 0.197) and the anxiety of being infected with Covid-19 among health workers at health centers in Pontianak City. ), the application of 3M (p value = 0.006) and a history of illness (p value = 0.039) with anxiety about being infected with Covid-19 among health workers at the Pontianak City Health Center.Conclusion : Based on the results of research that has been done, it proves that the factors associated with anxiety about Covid-19 infection in health workers at Pontianak City puskesmas are completeness of PPE, application of 3M and history of disease. It is hoped that there will be an evaluation of PPE provided for health workers and there is a need for monitoring in the use of PPE and consistency in the application of 3M during working time.Key words: Covid-19, Anxiety, Health Workers, Puskesmas